Ultrahigh anti-corrosion performance of polymer-based coating filled with a novel micro network nanofiller. (September 2021) - Zhang, Meng; Li, Cheng; Wang, Xiao; Peng, Jianwen; Yuan, Sicheng; Geng, Haolei; Zhou, Yixi; Gao, Yueyang; Wang, Huaiyuan
Graphical abstract: Highlights: A novel micro network nanofiller CNTs/LDH-MoO4 (CLM) was obtained. CLM filler greatly reduces the permeability of corrosive media through the coating. CLM filler traps chloride ions and releases corrosion inhibitor molybdate through the ion exchange process. CLM coating exhibits excellent anti-corrosion performance in both ordinary environment and harsh oxygen environment. Abstract: Designing fillers for high-performance anti-corrosion coatings, especially coatings suitable for harsh environments, remains a huge challenge. Herein, a novel micro network nanofiller CNTs/LDH-MoO4 (CLM) was successfully obtained by a facile in-situ growth method and employed to endow coating with excellent anti-corrosion performance. Electrochemical impedance spectroscopy (EIS) demonstrated the low frequency impedance value of the CLM coating maintained above 10 11 ohm·cm 2 during the 60 days of immersion in 3.5 wt.% NaCl solution. Surprisingly, the coating still exhibited superior anti-corrosion performance after being immersed for 10 days in the harsh environment where 3 MPa pure oxygen and 3.5 wt.% NaCl solution coexist.